Propriedades vibracionais de L-Treonina e D-Treonina sob altas pressões - Holanda, Rocicler Oliveira (2014)
In this work, crystals threonine (C4H9NO3) in the forms L and D were subjected to analysis by Raman spectroscopy. Initially there was an attempt to identify all of the Raman bands for the two samples by comparison with data from other work Raman spectroscopy of amino acids. In a second step we obtained the spectra of the material by varying the thermodynamic parameter hydrostatic pressure. For the D-threonine spectral experiments for the hydrostatic pressure due region was in the range of frequencies between approximately 30 cm-1 and 600 cm-1 and the change in pressure between 0.0 GPa and 8.5 GPa. The results show that the crystal D-threonine undergone two structural phase transitions, the first pressure range between 1.9 and 2.4 GPa and the second pressure range between 5.1 and 6.0 GPa. The crystals of the L-form were reviewed by the pressure of 27.0 GPa in the frequency range between approximately 50 cm-1 and 3300 cm-1. Changes associated with the external modes indicate that the material suffered three reversible phase transitions: the first at 1.6 GPa, 9.2 GPa in the second and a third at 15.5 GPa. A compared with a previous work on L-conformer is also provided.